Distributed Arithmetic for Efficient Base-Band Processing in Real-Time GNSS Software Receivers - Grégoire Waelchli; Marcel Baracchi-Frei; Cyril Botteron; Pierre-André Farine (Journal of Electrical and Computer Engineering)
The growing market of GNSS capable mobile devices is driving the interest of GNSS software solutions, as they can share many system resources (processor, memory), reducing both the size and the cost of their integration. Indeed, with the increasing performance of modern processors, it becomes now feasible to implement in software a multichannel GNSS receiver operating in real time. However, a major issue with this approach is the large computing resources required for the base-band processing, in particular for the correlation operations. Therefore, new algorithms need to be developed in order to reduce the overall complexity of the receiver architecture. Towards that aim, this paper first introduces the challenges of the software implementation of a GPS receiver, with a main focus given to the base-band processing and correlation operations. It then describes the already existing solutions and, from this, introduces a new algorithm based on distributed arithmetic.